A Collaborative Approach to Early Identification and Referral of Children Who are in Family Childcare Settings, Birth to Five, Born to Teenage Mothers - Yockelson, Suzanne; Linder, Cynthia; Asman, Rachel (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
Children of teenage mothers are at high risk for developmental delays, intellectual and learning disabilities, behavior disorders and school related problems [1]. Early identification and referral into prevention or early intervention programs may ameliorate that risk. Children of teen mothers who are in family childcare may not have access to routine developmental and behavioral screenings that would lead to early identification and referral. Members of an early childhood advisory board collaborated to conduct a screening event using the ASQ-3® and the ASQ:SE® at a local children’s museum for 26 children of teen mothers who had no previous access to developmental screenings. Parents completed the questionnaires while playing with their children at the museum. Nine of the children scored well within the range of typical development and 17 scored at or beyond the cut-off scores on the ASQ-3 and/or the ASQ:SE. Each child who scored at or beyond the cut-off received referrals for evaluation, parent and child programming and/or family support services. When there were concerns, families also received care coordination while all families received activities and a child’s book. The implications for this study suggest that collaborative efforts are effective in providing access to developmental screenings and referral into subsequent services for at-risk young children who are in family childcare settings.